The novels of Oleg Sagan-ool: ideologic and artistic innovation - Kombu, Saylykmaa S. (The New Research of Tuva, 2013)
Article reviews the life and works of the Tuvan literature classic writer Oleg Karlamovich Sagan-ool. Analysis of his novels is also present.
Keywords: O.K. Sagan-ool; classic; Tuvan literature; modernity; novelistic; artistic; discovery